The Role of Eosinophils in Liver DiseaseSummary - Linxi Xie; Hejiao Zhang; Long Xu (Cellular and Molecular Gastroenterology and Hepatology)
Previously, eosinophils were primarily regarded as effector toxic cells involved in allergic diseases and parasitic infections. Nevertheless, new research has shown that eosinophils are diverse and essential for immune regulation and tissue homeostasis. Their functional plasticity has been observed in patients with inflammatory diseases, cancer, infections, and other disorders. Although eosinophils are infrequently observed within the liver during periods of homeostasis, they are recruited to the liver in various liver diseases, including liver parasitosis, acute liver injury, autoimmune liver disease, and hepatocellular carcinoma. Furthermore, eosinophils have demonstrated the capacity to promote liver regeneration. This article explores the multifaceted roles of eosinophils in liver diseases, aiming to provide insights that could lead to more effective clinical therapies for these conditions.